The impact of joint venture between Technology Park Malaysia College Sdn Bhd and California Polytechnic University, Pomona, USA / Norhanis Mohd Hasim - Mohd Hasim, Norhanis (Faculty of Business and Management, 2010)
A joint venture is a business enterprise under-taken by two or more persons or organizations to share the expense and profit of a particular business project. "Joint ventures are not business organizations in the sense of proprietorship, partner-ships or corporations. International joint ventures in particular are becoming more popular, especially in capital-intensive industries such as oil and gas exploration, mineral extraction, and metals processing. The purpose for this study is to understand the reason of joint venture implementation, to describe the extent the TPM College benefits from the joint venture activities and to identify the activities that TPM College had done with Cal Poly University. The source of data will focus on the observation, interview and references which are related to the study. After all data has been gathered, it will be interpreted to make it sense for supporting the activities identified. The findings from this study will provide information that can be used for further investigation in the same nature of study or industry.